Building a Fab on a Chip - Imboden, M.; Han, H.; Stark, T.; Lowell, E.; Chang, J.; Pardo, F.; Bolle, C.; del Corro, P.G.; Bishop, D.J. (Royal Society of Chemistry, 2014)
Fil: del Corro, P.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina